Humour in Islam: A Philosophy Study of Humour - Syarifuddin, Syarifuddin (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Hadith is the second source of Islamic law after the Quran. Hadith was sourced from an interpretation of the practices of the deeds, words, and actions of Rasulullah SAW, as well as the application of Islamic teachings that are carried out in a factual and ideal manner. Muslims are expected to follow, apply, and practice it in their daily lives. Life needs humour; even humour and laughter are human nature that God has destined for humans. Humour is permissible in Islam; many texts of the Qur'an and Hadith allow it, and even the Prophet himself often joked and laughed with his companions. There are several reasons that the Messenger of Allah allowed reasonable humour, among them: being within limits and natural, not having lies, not insulting or slighting fellow Muslims, being far from fear and threats, knowing and being fit for the situation and conditions, and being within acceptable limits of common sense.